Species Composition and Ecology of Macrozoobenthos in The Shakhrikhonsoy Canal (Texas Journal of Agriculture and Biological Sciences, 2024)
This article is dedicated to studying the species composition and ecology of macrozoobenthos in the Shakhrikhonsoy Canal. During the research, the ecological state of the canal water was assessed based on the biological diversity of macrozoobenthos. A total of 23 identified species of macrozoobenthos were analyzed as ecological indicators, and their relationship with water quality was determined. Classes such as Gastropoda, Ephemeroptera, Plecoptera, and Hirudinea played a significant role in identifying the degree of organic pollution and ecological balance of the aquatic environment. The findings of the study serve as an essential foundation for the ecological monitoring of the Shakhrikhonsoy Canal, the management of biological resources, and the development of strategies for improving water quality